Complex systems in finance and econometrics - Meyers, Robert A. (Springer eBooks., 2011)
Complex Systems in Finance and Econometrics is an authoritative reference to the basic tools and concepts of complexity and systems theory as applied to an understanding of complex, financial-based business and social systems. Fractals, nonlinear time series modeling, cellular automata, game theory, network theory and statistical physics are among the essential tools and techniques for predicting, monitoring, evaluating, managing, and decision-making in a wide range of fields from health care, poverty alleviation, and energy and the environment, to manufacturing and quality assurance, model building, organizational learning. and macro and microeconomics. Sixty of the world?s leading experts present 47 articles for an audience of advanced undergraduate and graduate students, professors, and professionals in all of these fields.